Predicting Factors for Smoking Behavior among Women Who Frequent Nightlife Entertainment Venues around a University in the Northern Region of Thailand - Chakkraphan Phetphum; Boonchanuttha Pongpreecha; Jariya Hangsantea; Warangaungkana Muankaew (SAGE Publishing, 2018)
This cross-sectional survey aims to study the behaviors and predictors for smoking behaviors among women who frequent nightlife entertainment venues around a university in the northern region of Thailand. Samples comprised 279 women who visited nightlife venues around a university in the northern region of Thailand. A questionnaire was used for data collection. Data were analyzed by chi-square and binary logistic regression. The results found that women who frequented nightlife venues and smoked accounted for 32% and 22% of those who smoked inside such venues. Furthermore, the factors identified as predictive of smoking behavior among women who frequented nightlife entertainment venues included frequently visiting nightlife venues more than 3 days per week (odds ratio (OR) = 8.89, 95% confidence interval (CI): 3.31-23.90), having a positive attitude toward smoking (OR = 3.13, 95% CI: 1.56-6.28), having a smoking family member (OR = 2.78, 95% CI: 1.37-5.66), and having a smoking partner (OR = 4.86, 95% CI: 2.38-9.93). Therefore, relevant agencies should continuously promote the right attitudes about smoking to Thai women who frequent nightlife entertainment venues.